OPTIMIZATION OF THE TRICHODERMA HARZIANUM CuZn SUPEROXIDE DISMUTASE GENE EXPRESSION IN E. COLI - Yang*, Qian; Yang, Li-ming; Liu, Pi-Gang; Li, Sen; Li, Hu-lun (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2007)
A study of the optimization of CuZn superoxide dismutase gene expression in E. coli L21/pET28-SOD was undertaken. The SOD gene was directionally cloned into expression vector pET28.The recombinant plasmid was transformed into E. coli BL21 and induced by IPTG to express SOD protein. The four effective factors, including the initial concentration of BL21/pET28-SOD, concentration of IPTG, incubation temperature and induction time, were optimized during the induction of target protein. To detect the expression efficiency under different induction conditions, the total protein in the samples were subjected to SDS-PAGE. The SOD protein was successfully expressed in E. coli BL21/pET28-SOD. SOD expression was optimal at the following that E. coli BL21/pET28-SOD at OD600nm =0.6, IPTG 0.125 mmol/L, incubation at 37℃ and incubation for four hours. Keywords: SOD protein, expression, optimization Corresponding author: E-mail: YangQ@hit.edu.cn